The Price of Rice: Market Integration in Eighteenth-Century China - Cheung, Sui-wai (Center for East Asian Studies, Western Washington University, 2008)
The Price of Rice by Sui-wai Cheung investigates the grain tax, canal transportation, and market integration, to give a complete picture of the long-distance rice trade in China during the eighteenth century.